Nanocrystalline high‐entropy carbide ceramics with improved mechanical properties. Issue 1 (12th September 2021) - Ma, Mengdong; Sun, Yanan; Wu, Yingju; Zhao, Zhisheng; Ye, Li; Chu, Yanhui
Abstract: The nanocrystalline (Hf0.25 Zr0.25 Ta0.25 Ti0.25 )C high‐entropy carbide ceramics were successfully prepared through high‐pressure sintering of the self‐synthesized nanopowders for the first time. The results showed that the relative density, grain size, hardness, and elastic modulus of all the as‐prepared samples increased gradually with the increase of sintering temperatures from 1200 to 1600°C. The as‐fabricated samples at 1600°C possessed a relative density of 97.1% and a mean grain size of 98 ± 35 nm and simultaneously exhibited good comprehensive mechanical properties with Vickers hardness of 25.7 ± 0.6 GPa and fracture toughness of 4.3 ± 0.4 MPa·m 1/2 at room temperature due to the grain refinement strengthening mechanism and microcrack deflection and bridging toughening mechanism. In addition, they showed a linear decrease in high‐temperature Vickers hardness with the increase of the temperature from room temperature to 1000°C, which was determined by the combined effects of the intrinsic softening of HEC‐1 ceramics at elevated temperature and the presence of ZrO2 impurity phase at the grain boundaries.